2021
DOI: 10.1002/fsn3.2260
|View full text |Cite
|
Sign up to set email alerts
|

Detection of fraud in lime juice using pattern recognition techniques and FT‐IR spectroscopy

Abstract: The lime juice is one of the products that has always fallen victim to fraud by manufacturers for reducing the cost of products. The aim of this research was to determine fraud in distributed lime juice products from different factories in Iran. In this study, 101 samples were collected from markets and also prepared manually and finally derived into 5 classes as follows: two natural classes (Citrus limetta, Citrus aurantifolia), including 17 samples, and three reconstructed classes, including 84 samples (made… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…In our previous study, we revealed the capability of another portable NIRS (Tellspec ® , 900-1700 nm) and chemometrics approach for the discrimination of genuine and citric-adulterated lime juices with the accuracy of 88% for each PLS-DA and k-NN models (29). In addition, the feasibility of FT-IR spectroscopy and chemometrics approach in the detection of adulterated lime juice (prepared by lime juice concentrates) was revealed in a study conducted by Mohammadian et al The lime juice samples were correctly designated to their original groups using PLS-DA and counter propagation artificial neural networks (CPANN) maps with an overall accuracy of 87% in the validation procedure (12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous study, we revealed the capability of another portable NIRS (Tellspec ® , 900-1700 nm) and chemometrics approach for the discrimination of genuine and citric-adulterated lime juices with the accuracy of 88% for each PLS-DA and k-NN models (29). In addition, the feasibility of FT-IR spectroscopy and chemometrics approach in the detection of adulterated lime juice (prepared by lime juice concentrates) was revealed in a study conducted by Mohammadian et al The lime juice samples were correctly designated to their original groups using PLS-DA and counter propagation artificial neural networks (CPANN) maps with an overall accuracy of 87% in the validation procedure (12).…”
Section: Discussionmentioning
confidence: 99%
“…For instance: The Chinese milk scandal where the milk products and infant formula were adulterated with melamine (4,5), the contamination of chili powder with dye (6), several cases of the adulteration of spices with ground materials (7), the Irish pork crisis (8), the horse-meat scandal (9), adulteration of olive oil with hazelnut oil (10) and honey made from an artificial sweetener (11) are just some examples. Besides, several cases of adulteration in fruit juices have been detected in recent years (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…For example, high-performance liquid chromatography (HPLC) , and Fourier transform infrared spectroscopy (FTIR) , have been tested for citrus juice authenticity when coupled with machine learning. Specifically, FTIR has been evaluated against a variety of pure or adulterated fruit juice samples. However, a common limitation to untargeted instrumental approaches is the requirement of expensive instrumentation to have variable turnover rates, which were generally demonstrated using limited sample sizes. ,,,,, Thus, it is necessary to devise novel and alternative approaches with low-cost, simplistic, and high-throughput capabilities for rapid screening. Recently, the combination of nanotechnology with nucleic acids has made tremendous ground for medicinal and biosensing applications. An advantage of nanoparticle-based biosensor formulations is the bulk scale production using low-cost natural precursors, and inexpensive simple benchtop spectrometers for data collection, which can expedite untargeted detection efforts.…”
Section: Introductionmentioning
confidence: 99%
“…The purpose of choosing this model is its capability to combine both unsupervised and supervised learning. In Addition, the CP-ANNs are a popular network [16] and are extensively used in numerous areas [17][18][19] through their abilities to solve the issues of classification, clustering, and recognition tasks. Moreover, pattern recognition comprises two learning modes (Unsupervised and supervised) [20].…”
Section: Introductionmentioning
confidence: 99%